Inspirations on Virus Replication and Cell-to-Cell Movement from Studies Examining the Cytopathology Induced by Lettuce infectious yellows virus in Plant Cells - Qiao, Wenjie; Medina, Vicente; Falk, Bryce W. (Frontiers in Plant Science, 2017)
Lettuce infectious yellows virus (LIYV) is the type member of the genus Crinivirus in the family Closteroviridae. Like many other positive-strand RNA viruses, LIYV infections induce a number of cytopathic changes in plant cells, of which the two most characteristic are: Beet yellows virus-type inclusion bodies composed of vesicles derived from cytoplasmic membranes; and conical plasmalemma deposits (PLDs) located at the plasmalemma over plasmodesmata pit fields. The former are not only found in various closterovirus infections, but similar structures are known as ‘viral factories’ or viroplasms in cells infected with diverse types of animal and plant viruses. These are generally sites of virus replication, virion assembly and in some cases are involved in cell-to-cell transport. By contrast, PLDs induced by the LIYV-encoded P26 non-virion protein are not involved in replication but are speculated to have roles in virus intercellular movement. These deposits often harbor LIYV virions arranged to be perpendicular to the plasma membrane over plasmodesmata, and our recent studies show that P26 is required for LIYV systemic plant infection. The functional mechanism of how LIYV P26 facilitates intercellular movement remains unclear, however, research on other plant viruses provides some insights on the possible ways of viral intercellular movement through targeting and modifying plasmodesmata via interactions between plant cellular components and viral-encoded factors. In summary, beginning with LIYV, we review the studies that have uncovered the biological determinants giving rise to these cytopathological effects and their importance in viral replication, virion assembly and intercellular movement during the plant infection by closteroviruses, and compare these findings with those for other positive-strand RNA viruses.